Impact of thermal aging on the intermetallic compound particle size and mechanical properties of lead free solder for green electronics. (November 2017) - Aamir, Muhammad; Muhammad, Riaz; Ahmed, Naseer; Waqas, Muhammad
Abstract: The Sn-Ag 3 . 0 -Cu 0 . 5 lead free solder ( LFS ) alloy is mostly used as good alternative as compared to conventional Tin-Lead ( Sn-Pb ) due to its good mechanical properties and no harmful effect on environment but it stills has some problems to be solved regarding the growth formation of intermetallic compounds ( IMCs ). The IMCs present inside the bulk tin ( Sn ) matrix grow at high temperature and hence their impact on mechanical properties becomes more significant. In this work the effects of lanthanum ( La ) doping of Sn-Ag 3 . 0 -Cu 0 . 5 is investigated as function of IMCs growth and mechanical properties including yield strength ( YS ) and ultimate tensile strength ( UTS ) under different thermal aging temperatures. The selected La concentration in this study is 0.4 wt%. The aging time is 50 h and thermal aging temperatures are 60 °C, 100 °C and 140 °C. The microstructure examination before and after thermal aging is observed using scanning electron microscopy ( SEM ) followed by image analysis to estimate the nature of IMCs . The chemical composition is confirmed with energy dispersive X-ray ( EDX ). The YS and UTS are also examined before and after thermal aging for the un-doped and doped samples from stress-strain curves using universal testing machine ( UTM ). It is investigated that inclusion of 0.4 wt% La into Sn-Ag 3 . 0 -Cu 0 . 5 solder system results in increasing the IMCs growth rate and hence mechanical properties reduced. It is also observed that the microstructure becomes coarsen after thermal aging due to growth of average IMCs particle size with significant decrease in YS and UTS . Further, mathematical relations with minimum error are developed to predict mechanical properties ( YS and UTS ) at various levels of aging temperature, showing a reciprocal relationship between aging temperature and mechanical properties. Highlights: La doped Sn-Ag3.0 -Cu0.5 is investigated in terms of IMCs and mechanical properties at different aging temperatures Thermal aging results in coarsen microstructure, increase in IMCs and decrease in mechanical properties La concentration less than 0.4 wt% is necessary for restriction of IMCs growth and better mechanical properties Mathematical relations are also presented for the prediction of mechanical properties at thermally aged temperatures